Application Of Pre And Post Conference In The Maternity Ward Wisma Tulip 4 Prof. Soerojo Hospital Magelang - Muadi, Muadi; Sulistya, Ghifa Triassukma (INDOGENIUS, 2025)
Background & Objective:   Law No.17 of 2023 defines a hospital as a health service institution that provides comprehensive personal health services, including inpatient, outpatient, and emergency care.  Method: This study used a qualitative case study method with direct observation for 10 days in the Maternity Ward Wisma Tulip 4, Prof. Soerojo Hospital Magelang, to evaluate the implementation of Pre and Post Conference and the influencing factors. Result: The findings indicated that issues remain in the implementation of pre and post conferences during patient handovers, where execution has not been optimal. The main problems identified were suboptimal implementation influenced by limited human resources and time constraints. As an improvement step, education for nurses and midwives regarding SOPs of pre and post conferences was planned, although challenges in implementation persisted. Conclusion: It is recommended that this report be utilized by the Management of Prof. Dr. Soerojo Psychiatric Hospital as an evaluation material to enhance the management function in implementing the Professional Nursing Practice Model (PNPM).